2 Handfuls of Medication in 2 Hours Just to Let Him Talk (Bangladesh Journal of Medical Science, 2014)
Repeated dose of adrenaline in anaphylaxis is limited evidence in clinical setting. Hence, the usage is depending on physician best interest and knowledge. We reported a case of repeated doses of adrenalin was given through nebulizer and intravenous in anaphylaxis. We believed the unusual circumstances of this case was likely to be repeated on some readers' clinical practice and this mode of treatment is an adjunct to consider in such cases especially in Emergency Department (ED). DOI: http://dx.doi.org/10.3329/bjms.v13i2.16100 Bangladesh Journal of Medical Science Vol.13(2) 2014 p.209-211